Preparation of a titanium-functionalized polymeric material rich in hydrophilic groups for phosphoproteome and glycoproteome analyses in serum - Sheng, Xiuqin; Chen, Jiakai; Shao, Jiahui; Zhang, Xiaoya; Wang, Bing; Ding, Chuan-Fan; Yan, Yinghua (Analyst (London), 2025)
The analysis of protein phosphorylation and glycosylation is critical for investigating disease development. In this work, 1,2-epoxy-5-hexene and N , N -methylenebisacrylamide were polymerized with vinyl phosphate to produce a polymer (denoted as PVME), which contained a variety of hydrophilic groups. The material's hydrophilicity was further enhanced by a ring-opening reaction with cysteine (the product was denoted as Cys-PVEM). Finally, titanium sulfate was combined with Cys-PVME to form titanium-rich polymers ( Cys-PVME-Ti 4+ ) for the enrichment of phosphopeptides and glycopeptides. Cys-PVME-Ti 4+ has a good sensitivity (0.02 fmol) and selectivity (1 : 1000) with a loading capacity of 62 mg g −1 , recyclability (9 cycles), and a good recovery rate (101.6 ± 0.60%) for phosphopeptides, and good sensitivity (0.01 fmol μL −1 ), selectivity (1 : 2000), a loading capacity of 62.5 mg g −1 , recyclability (9 cycles), and a good recovery rate (98.7 ± 1.2%) for glycopeptides. In addition, after enrichment with this material, 27 phosphopeptides with 14 phosphoproteins and 223 glycopeptides associated with 88 glycoproteins were captured from the serum of colorectal cancer patients, while 27 phosphopeptides associated with 14 phosphoproteins and 210 glycopeptides associated with 111 glycoproteins were also captured from the serum of a normal control. Gene ontology (GO) analysis revealed that complement activation, extracellular region, extracellular space, blood coagulation, the IgG immunoglobulin complex, and heparin binding were different between normal control and colorectal cancer, implying that related pathways are likely involved in colorectal cancer pathogenesis. This work introduces a titanium-functionalized polymeric material rich in hydrophilic groups for phosphopeptide and glycopeptide enrichment in serum.